KAJIAN PENGERINGAN LATEKS DENGAN UNIT PENGERING BERTENAGA LISTRIK PADA PENGOLAHAN KARET (Heven brassiliensis) - Hervian Rahardiansyah; Iwan Taruna; Siswoyo Soekarno (JURNAL AGROTEKNOLOGI, 2014)
This study was purposed to design and construct a prototype electric-powered dryer unit for drying of Rubber Smoked Sheet (RSS). The performance of designated dryer was examined in terms of drying conditioning and the quality of RSS and then compared to original curing process based on the sheet quality and pace of drying. The results showed that the dryer was capable to produce the standard quality of RSS, as indicated by the absences of bubbles, product defects and impurities. The prototype of drying unit could reduce also the weight of RSS or latex rubber in average of about 36% of the initial weight for about 48 hours at temperature range between 56 and 76°C.Keywords: drying unit, latex sheet, sheet quality